Penerapan Metode Capacitated Maximum Covering Location Problem (CMCLP) dalam Penentuan Lokasi Tempat Penampungan Sementara (TPS) - Firmansyah, Fajar Muchti; Nuha, Hilyatun; Murnawan, Hery (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Mantup Sub-district, Lamongan Regency has 7 Temporary Waste Storagea Facilities (TPS) that are not intergrated with the Final Disposal Site (TPA) and have not served 72 hamlets or waste source. This causes piles of waste in the TPS area and several public places. Determinig the loction of the TPS aims to opimize the TPS service so that it can serve all waste sources with the mathematical model of the Capacitated Maxium Covering Location Problem (CMCLP) and is solved using Google Colab in the Python programming language. The data collected in this study include the points of waste sources and TPS along with the distance between the two points, the capacity of waste transport vehicles, and the amount of waste produced based on SNI-19-3964-1994 sampling. The model results show that there are 8 optimal TPS locations consisting of 3 TPS that have been built and 5 alternative TPS that can serve 72 waste sources with maximum service covereage of 4 kilometers.